Clinical Updates on the Aortic Aneurysm and Aortic Dissection (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Aortic aneurysms and aortic dissections are potentially life-threatening conditions that require urgent attention. In recent years, a substantial amount of research has been conducted. Despite advances in diagnosis and treatment, there are significant treatment gaps that need to be addressed to save lives. One major gap is the early detection and diagnosis of aortic aneurysms, as they often present no symptoms until a catastrophic event occurs. Increased awareness and effective screening programs are crucial to identify at-risk individuals. With decreasing incidence in the Western world, cost–benefit analyses or more targeted screening methods are becoming increasingly important. Similarly, there is a need for timely recognition and diagnosis of aortic dissections, as symptoms can be easily mistaken for other conditions. Medical professionals must be equipped with the necessary knowledge and tools for prompt identification. Bridging these gaps requires optimizing treatment strategies, refining surgical approaches, and developing novel therapies. Comprehensive long-term management strategies are also essential for individuals who have survived aortic dissections. Standardized guidelines and protocols for post-dissection care, including regular imaging studies and medication management, are vital for optimal outcomes. From the genetic analysis of aortic patients, to innovative clinical case studies, and real-world long-term outcomes, this collection of articles deals with manifold aspects of aortic disease and therapy.